Detoxification of Chemical Warfare Agents From WWI to Multifunctional Nanocomposite Approaches - Giannakoudakis, Dimitrios A. (Cham : Springer International Publishing, 2018)
This book presents a detailed history of chemical warfare development during the First World War and discusses design approaches to gas masks and the performance of new filter materials that decontaminate chemical warfare agents (CWA) when applied in the vapor phase. It describes multifunctional nanocomposites containing zinc and zirconium (hydr)oxides, graphite oxide and silver or gold nanoparticles as reactive adsorbents for the degradation of the CWAs vapors. In addition it examines in detail the surface properties that are most important in the mineralization performance.
Chemical Warfare Agents (CWAs) -- World War I: Militarization of chemistry -- Mustard Gas: The King of CWAs -- Current protection against CWAs -- New approaches in the detoxification of CWAs -- Path towards future research.
Chemistry and Materials Science
text file PDF
Keywords: Nanotechnology; Environmental chemistry; Catalysis; Chemistry-History.